Anatomy-based characteristics of far-field SVC electrograms in right superior pulmonary veins after isolation. (31st December 2022) - Gu, Wentao; Liu, Weizhuo; Li, Jian; Shen, Jun; Pan, Jiawei; Wu, Bangwei; Shi, Haiming; Luo, Xinping; Xiong, Nanqing
Abstract: Background . Far-field electrograms from superior vena cava (SVC) can be present in right superior pulmonary vein (RSPV) after pulmonary vein (PV) isolation. Objectives . To analyze the characteristics of far-field SVC potentials in RSPV after PV isolation and the local anatomy difference between patients with and without the potentials. Methods . Patients undergoing PV isolation were retrospectively reviewed, contrast-enhanced computed tomography (CT) was performed before procedure for observing the anatomical relationship between RSPV and SVC. The prevalence and characteristics of far-field SVC electrograms were described and compared to far-field left atrial potentials at the nearest point along the linear ablation lesion. The anatomical proximity of RSPV and SVC on a 2-dimensional horizontal CT view was compared between patients with and without far-field SVC potentials. Results . Far-field SVC electrograms were observed in 35/92(38%) patients with an amplitude of 0.24 ± 0.11 mV and a major deflection slope of 0.051 ± 0.036 mV, both significantly higher than far-field left atrial electrograms ( p  < .001). In patients with far-field SVC electrograms, 83% had connected RSPV-SVC, defined as distance between RSPV and SVC endocardium less than 3 mm at the layer of RSPV ostium roof, while in patients without far-field SVC electrograms, 70% had disconnected RSPV-SVC. Conclusions . Far-field SVC electrograms appeared in RSPV had a prevalence higher than previously reported and a sharper major deflection compared to far-field left atrial electrograms. Connected RSPV-SVC on CT was associated with the presence of far-field SVC electrograms.